Analysis of detonation wave effect in radial water coupling blasting - Yanbing WANG; Weiwen KONG; Dongchen WANG; Youyi SHEN; Ajian FENG; Yang LI; Wenhai ZHENG (Meitan xuebao)
To study the influence of different water coupling coefficients and coupling forms on the blasting effect, theoretical derivation and high-speed schlieren experiments were conducted, combined with AUTODYN numerical simulation, to analyze the evolution process of the detonation flow field. The wall pressure of the blast hole in two coupling forms of concentric and eccentric during water medium coupling blasting was derived; Five types of explosive packages with different water coupling coefficients and coupling forms were designed. The detonation wave process inside the explosive was obtained through schlieren experiments and numerical simulations. The pressure changes, propagation, and energy transfer efficiency of the shock wave were compared and analyzed under these five conditions. The results indicate that the water coupling coefficient and coupling form greatly affect the transmission efficiency of explosion energy, and there is an optimal decoupling coefficient that cannot be blindly increased. Due to the different water coupling coefficients and forms, the explosion energy contained in the transmission of shock waves into the free air field varies, which in turn affects the magnitude of peak pressure. As the water coupling coefficient increases, the pressure on the borehole wall first increases and then decreases, and the energy transfer efficiency first decreases, then increases and then decreases; Due to the presence of water medium, water coupled charge blasting can effectively extend the duration of shock wave action and improve energy transfer efficiency; Compared to the concentric water coupling charge form, the eccentric water coupling charge has a significant eccentric stress field, which can significantly increase the peak pressure of the hole wall on the coupling side, reduce the energy attenuation efficiency, and improve the energy utilization rate. The blasting effect on the coupling side is better than that on the concentric coupling. The research results have certain theoretical guidance and reference value for the application of water coupled charge blasting in slope excavation, tunnel surrounding blasting, and improving blasting effects.